Eskimo boyhood : an autobiography in psychosocial perspective - Kakianak, Nathan (Studies in anthropology (Lexington, Ky.), 1974)
Here is a unique view of life as experienced by a young Eskimo. The autobiography was written by a youth in his early twenties who relates the details of his boyhood life, recalling the feelings accompanying his experiences. In addition to allowing Nathan simply to relate his story thereby illustrating the uniqueness of an individual life, Mr. Hughes sets the autobiography in a broader context, which illustrates the major trends in sociocultural changes in a small and isolated corner of the world. Not only were different answers required in this new evolving world, but different questions ...